Diagnostic-Therapeutic Pathway and Outcomes of Early Stage NSCLC: a Focus on EGFR Testing in the Real-World - Pasello, Giulia; Lorenzi, Martina; Pretelli, Giulia; Comacchio, Giovanni Maria; Pezzuto, Federica; Schiavon, Marco; Buja, Alessandra; Frega, Stefano; Bonanno, Laura; Guarneri, Valentina; Calabrese, Fiorella; Rea, Federico (Frontiers in Oncology, 2022)
Background Osimertinib is considered the standard-of-care for previously-untreated EGFR mutant advanced non-small cell lung cancer (NSCLC). Oncogene driver screening in early NSCLC is not standard practice. A real-world study has been designed in order to investigate the optimal testing frequency and timing for EGFR mutations in early NSCLC in clinical practice. Patients and Methods The present observational, retrospective study evaluated the real-world diagnostic-therapeutic pathway and clinical outcomes of 225 patients with stage I-III NSCLC, with particular reference to the EGFR-mutant subgroup. Results Prior to surgery, 101 patients had undergone a diagnostic biopsy; EGFR mutational analysis was available in 56 (55%) patients and 12 patients (21%) had a cancer harboring an EGFR mutation. Among surgical specimens, reflex EGFR test was performed in 181 (80%) of 225 and 35 cases (19%) were EGFR mutant. The majority of patients had not received adjuvant chemotherapy (N=174, 77%) or adjuvant radiotherapy (N=201, 89%). Of 49 (22%) patients experiencing disease relapse, 26 (53%) received first-line systemic treatment. All EGFR-mutant relapsed patients (N=6, 12.2%) received an EGFR-TKI. Median overall survival (OS) and relapse-free survival for the entire population were not reached. Multivariate analysis for OS confirmed a significant correlation with age, female gender, EGFR status, necrosis score, perineural invasion, and relapsed disease. EGFR test costs represented 1.6-2.4% of the total costs of management per patient (€34,340). Conclusions Our results suggest that the frequency of EGFR mutations in early stage (I-III) NSCLC is similar to that of advanced stages. Reflex EGFR testing in all early-stage NSCLC at diagnosis or after surgery appears to be a valid tool to give patients the chance to benefit from targeted adjuvant treatment.